2020
DOI: 10.3389/fpsyg.2020.549628
|View full text |Cite
|
Sign up to set email alerts
|

Wayfinding in Interior Environments: An Integrative Review

Abstract: Wayfinding is an issue in complex facilities-including hospitals, airports, and office buildings-and wayfinding difficulties are associated with negative psychological and physiological consequences. In addition, since finding one's way in a building is a prerequisite for successfully using that building, wayfinding has attracted the attention of scholars and decision makers. The goal of this article is to review and synthesize the published literature on wayfinding in interior environments. A systematic searc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0
5

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(28 citation statements)
references
References 111 publications
(360 reference statements)
0
23
0
5
Order By: Relevance
“…Research has identified several heuristics pedestrians may use to make route choices ( table 1 and see [ 69 ] for a review). One type of heuristic can be described as one-reason heuristics that assume pedestrians only use one cue (principle, rule, criteria or strategy) to compare alternatives for decision making and focus on the characteristic of the route.…”
Section: Principles Of Pedestrian Route Choicementioning
confidence: 99%
“…Research has identified several heuristics pedestrians may use to make route choices ( table 1 and see [ 69 ] for a review). One type of heuristic can be described as one-reason heuristics that assume pedestrians only use one cue (principle, rule, criteria or strategy) to compare alternatives for decision making and focus on the characteristic of the route.…”
Section: Principles Of Pedestrian Route Choicementioning
confidence: 99%
“…The authors of [16], by examining the case of two metro stations in Brussels, specified that the main reasons are the absence of direct sunlight and the lack of recognizable spatial features, while the authors of [17] studied the case of Hong Kong, pointing out that most passengers lose their orientation during the vertical travel between different levels. The most common way to minimize the negative influence discussed above is to install directional signs and maps to help the passengers understand their orientation [18]. Nevertheless, to search for directional guidance itself may be a difficult wayfinding task, especially for the passengers with deficits in either mobility or spatial memory.…”
Section: Spatial Orientation and Wayfinding In Metro Stationmentioning
confidence: 99%
“…Jamshidi et al explored the complex factors of wayfinding in indoor environments through a review and emphasized that wayfinding involves human cognitive processes and behaviors. The review study identified two factors that influence wayfinding: (a) user factors and (b) environmental factors (Jamshidi et al, 2020). To explore the extent to which knowledge of the wayfinding domain is established and related concepts, the following section provides a brief review of research related to the field of wayfinding based on these two factors.…”
Section: Introductionmentioning
confidence: 99%
“…These literature reviews provide an exhaustive analysis of a specific topic. As mentioned above, Jamshidi et al, reviewed the published literature on indoor wayfinding and identified two major factors in indoor wayfinding, namely (a) user factors and (b) environmental factors (Jamshidi et al, 2020). Dalton et al explored that the role of social factors in wayfinding is important for both basic research and applications.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation